A Comparative Study of Durvadi Taila and Panchvalkal Ointment in Post Operative Wound Healing - Trivedi, Diksha; Kumar, Hemant (International Research Journal of Ayurveda & Yoga, 2021)
A healthy lifetime of 100 years has been the cherished wish of humanity from antiquity. This has been considered essential to realize the four principal instincts of life namely Dharma, Artha, Kama and Moksha. Only the absence of illness isn’t defined as health. Today it’s defined as comprehensive state of well being which refers to physical, mental, spiritual and social well being of a person (W.H.O.’s definition of health), which is extremely almost like definition of Swastha- healthy person given by Acharya Sushruta. One of the most important branches of Ayurveda is Shalya Tantra in which various surgical and para-surgical procedures have been described. Vrana is one among of them. The main aim of this paper is to assess the efficacy of the trail drugs i.e. Durvadi Taila and Panchvalkal Ointment on post-operative wounds. The most widely and vitally explained chapter of Shalya Tantra is vrana. Classification of Vrana, Nadi Vrana, Shuddha Vrana, Dagdha Vrana, Sadhya Vrana etc., their prognostic evaluation and management with Shasthi Upkrama i.e. from Aptarpana to Rakshavidhana, continuous suturing in clean wounds (Shuddha Vrana), avoidance of sepsis (Dushta Vrana) and excision (Chhedana) of expelled out omentum and careful suturing of perforation of intestine within the management of perforating wounds of abdomen, etc. are remarkable for their modern outlook.